Implementation of an Automated Trading System for XAG/USD Using Donchian Channel and Safe-F Risk Management on MetaTrader 5 - Sirait, Andreas Martin Raja; Rahman, Haikal; Syah, Dedy Husrizal (Economic: Journal Economic and Business, 2025)
This study aims to develop and evaluate an Expert Advisor (EA) based on the Donchian Channel indicator combined with the Safe-F Money Management strategy for trading the XAG/USD pair using the MetaTrader 5 platform. The EA is designed to capture breakout opportunities while adaptively managing trade size based on account balance. Testing was conducted using two approaches: backtesting with four years of historical data and real-time testing under actual market conditions. The backtesting results indicate that the H1 time frame scenario yielded more stable performance, with a Sharpe Ratio of 1.26 and low drawdown. In contrast, the real-time testing recorded less optimal outcomes, with profit factors below 1 and net losses in both scenarios. These findings suggest that although the EA performs well in simulations, real-time performance is affected by market volatility and execution factors. Therefore, further optimization and broader testing are recommended to enhance the system’s resilience in dynamic market environments.